Student Perception of Project Based Learning (PjBL) Learning Model by Developing Creative Thinking Skills in Vocational High Schools - Mutia Liana; Rambat Nur Sasongko; Muhammad Kristiawan; Reny Dwi Riastuti (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Vocational High School students are students who are required to independently produce innovative products, so they are ready to jump in the world of work. The product of a good project is a product produced from students who have creative thinking skills, so the purpose of research is to measure students' perception of the Project ased Learning (PjBL) learning model by developing creative thinking skills. The method used in this study is qualitative descriptive with longitudinal survey case studies. The subject of this study is a student of SMK N 3 Lubuklinggau City on the subject of Broad-Based Network Technology. Data collection techniques use questionnaire sheets and student perception interview sheets. Data analysis on questionnaires using descriptive analysis and interview results are analyzed by reducing questions and answers that are in accordance with the focus of the research. The results showed that students' perception of the Project ased Learning (PjBL) learning model by developing creative thinking skills got a score of 81% with a good category.